TEACHING FOREIGN LANGUAGE TO FUTURE AGRONOMISTS: FEATURES TO CONSIDER - Holovko, Iryna (Sworld-Us Conference proceedings, 2023)
The article depicts some approaches of organizing the process of teaching a foreign language to students of the specialty “Agronomy” taking into account the psycholinguistic peculiarities of speech perception, understanding, absorption and communicating i